Real time object customization in cad software via visual basic programming - Zainal Fahmi, Zainol Abidin; M. Nafis, O. Z. (Centre for Advanced Research on Energy, 2018)
This paper outlines a development of graphical user interface (GUI) for object customization in computer aided design (CAD) by utilizing Visual Basic (VB) programming language in NX10 CAD software. Major works involve development of the object customization tool in the form of new GUI which provides a set of editable parameters section. A customized graphical user interface (GUI) was developed to simplify the manual customization process. Initially, customization work is translated into programming codes via advanced tool available in the NX10. The recorded codes translated into visual basic script files and then is modified to create a functional GUI. The results revealed that the developed programs are capable to simplify drawing work in CAD by reducing the drawing steps and time.